2021
DOI: 10.3390/antibiotics10101145
|View full text |Cite
|
Sign up to set email alerts
|

Superinfection with Difficult-to-Treat Pathogens Significantly Reduces the Outcome of Periprosthetic Joint Infections

Abstract: Periprosthetic joint infection (PJI) is a serious complication after total joint arthroplasty. In the course of a PJI, superinfections with pathogens that do not match the primary infecting micro-organism may occur. To our knowledge, there are no published data on the outcome of such infections in the literature. The aim of this study was to assess the outcome of PJI with superinfections with a difficult-to-treat (DTT) pathogen. Data of 169 consecutive patients with PJI were retrospectively analyzed in this si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In the context of arthroplasty, Darwich et al found that 23.7% of 169 periprosthetic joint infections (PJIs) eventually evolved into superinfections with a new organism. The authors then showed that patients with superinfections had worse outcomes in terms of infection eradication, therapy failure, number of revisions, and mortality [19]. While our series showed a lower rate of superinfection than Darwich et al's, we deemed nine cases as indeterminable.…”
Section: Discussionmentioning
confidence: 49%
“…In the context of arthroplasty, Darwich et al found that 23.7% of 169 periprosthetic joint infections (PJIs) eventually evolved into superinfections with a new organism. The authors then showed that patients with superinfections had worse outcomes in terms of infection eradication, therapy failure, number of revisions, and mortality [19]. While our series showed a lower rate of superinfection than Darwich et al's, we deemed nine cases as indeterminable.…”
Section: Discussionmentioning
confidence: 49%
“…Differentiating aspects of treatment included utilisation of intravenous anti-fungal agents, topical anti-fungal use in cement spacer, and extended duration of antibiotics post second stage revision arthroplasty. One case in the post-MDT group involved a patient with a chronic PJI involving polymicrobial growth which included Candida albicans , MRSA and Aspergillus niger — all of which are known difficult-to-treat organisms [ 33 ]. This patient over a 2.5-year period underwent 8 operations given the number of recurrent episodes of PJI.…”
Section: Discussionmentioning
confidence: 99%
“…This patient over a 2.5-year period underwent 8 operations given the number of recurrent episodes of PJI. Given PJI broad presentation, including whether they involve difficult-to-treat organisms, comparison does become difficult as outcome from set management may be confounded by a multitude of factors [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug-resistant bacteria complicate adequate antibiotic therapy. In particular, the antibiotic treatment of PJIs caused by biofilm-forming pathogens that are resistant to biofilm-active antibiotics is a particular challenge: because fluoroquinolones target biofilm-forming Gram-negative bacteria and rifampicin targets biofilm-forming Gram-positive bacteria, rifampicin-resistant pathogens and fluoroquinolone-resistant Gram-negative bacteria are considered difficult-to-treat bacteria [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%